ANALISIS JEJARING FARMAKOLOGI DAUN TEMBELEKAN (Lantana camara L.) TERHADAP ANTI LUKA BAKAR - Tri Diana Puspita Rini; Wardah Salsabila Rafli; Rissa Maharani Dewi; Meki Pranata (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Burn injuries are skin lesions that can cause tissue damage, infection, and impaired regeneration if not properly treated. Lantana camara L. leaves are known to contain various secondary metabolites with potential wound-healing properties. This study aimed to analyze the anti-burn potential of Lantana camara using a network pharmacology approach. Computational analyses were performed using the KNApSACK, SwissADME, SwissTargetPrediction, GeneCards, STRING-DB, Cytoscape–CytoHubba, and ShinyGO 0.77 databases. A total of 39 secondary metabolites were identified, all of which fulfilled Lipinski’s Rule of Five, indicating good potential oral bioavailability. Protein target analysis revealed 305 intersecting proteins between metabolite targets and burn-related proteins. Network analysis identified AKT1 as the main hub protein, followed by TNF, IL6, STAT3, BCL2, HIF1A, and EGFR. The major biological pathways involved included the PI3K/Akt and HIF-1 signaling pathways, which regulate cell proliferation, angiogenesis, anti-apoptosis, and hypoxia response. In addition, positive regulation of peptidyl-serine phosphorylation was identified as the dominant biological process associated with inflammation regulation and tissue regeneration. These findings suggest that Lantana camara has strong potential as an anti-burn agent through a multitarget mechanism that supports tissue healing.